Morphotectonic Processes in Seismic Zones of Moderate (Global Journal of Human-Social Science, 2023)
This study deals with the neotectonic deformation in seismic zones of moderate intensity in some areas of the Sierras Pampeanas Santa B rbara System and Chaque a Plain of Argentina In the study region the location of earthquakes of three four and six Richter magnitudes agree with the traces of regional faults evidencing their neotectonic activity Seismic energy is generally transmitted over inherited faults such as in the Metan basin Minor new faults occur in Quaternary terraced deposits and others move taking advantage of the Neogene sedimentary strata The folds are generally buried but the younger sequences are gently undulating The seismic energy dissipated through fewer cohesion materials that form the valleys fill developing discrete fault scarps and strongly folded conglomerate strata The foothills deposits and basins absorbed most of the seismic energy released during the reactivation of the faults Tectonic activity is deforming 630 BP deposits in the Cumbres Calchaqu es piedmont
Keywords: neotectonics earthquakes andean foreland natural hazards